A OBSERVAÇÃO DE AVES E O BEM VIVER NA MELHOR IDADE: UM ESTUDO DE CASO NO PORTAL DA ROTA BIOCEÂNICA, CAMPO GRANDE-MS - SANTOS, JOANA DARC DOS; Benites, Maristela; Mamede, Simone (ANAIS DO ENIC, 2026)
.